A Triterpene Lactone from Callistemon citrinus Inhibits the PANC‐1 Human Pancreatic Cancer Cells Viability through Suppression of Unfolded Protein Response. Issue 10 (30th September 2020) - Tawila, Ahmed M.; Sun, Sijia; Kim, Min Jo; Omar, Ashraf M.; Dibwe, Dya Fita; Awale, Suresh
Abstract: Human pancreatic tumor cells such as PANC‐1 are known for their ability to tolerate nutrient starvation and thrive under the hypovascular tumor microenvironment, a phenomenon termed as 'austerity'. A search of agents that preferentially inhibit the cancer cell viability under the starvation condition without toxicity in the nutrient‐rich condition is a promising approach in anticancer drug discovery. In this study, a triterpene lactone, 3 β ‐hydroxy‐13, 28‐epoxyurs‐11‐en‐28‐one (ursenolide), isolated from a Callistemon citrinus extract has shown strong preferential cytotoxicity against PANC‐1 cells under nutrient starvation with PC50 value of 0.4 μm . Ursenolide‐induced rounding of PANC‐1 cell morphology followed by rupture of the cell membrane leading to cell death. In a real‐time cell migration study, ursenolide was found to inhibit PANC‐1 cell migration significantly. Mechanistically, it inhibited GRP78 and GRP94 under the starvation condition suggesting inhibition of unfolded protein response (UPR), an adaptive process of cell survival during starvation. It also inhibited the phosphorylation of the key survival protein Akt and mTOR. Overall results suggested that ursenolide is a potential anticancer agent against pancreatic cancer. Abstract :